SMAD dependent signaling plays a detrimental role in a fly model of SMARCB1-deficiency and the biology of atypical teratoid/rhabdoid tumors - Jeibmann, Astrid; Johann, Pascal-David; Pfister, Stefan; Kool, Marcel (Journal of neuro-oncology, 2017)
Atypical teratoid/rhabdoid tumors (ATRT) are highly malignant brain tumors arising in young children. The majority of ATRT is characterized by inactivation of the chromatin remodeling complex member SMARCB1 (INI1/hSNF5). Little is known, however, on downstream pathways involved in the detrimental effects of SMARCB1 deficiency which might also represent targets for treatment. Using Drosophila melanogaster and the Gal4-UAS system, modifier screens were performed in order to identify the role of SMAD dependent signaling in the lethal phenotype associated with knockdown of snr1, the fly homolog of SMARCB1. Expression and functional role of human homologs was next investigated in ATRT tumor samples and SMARCB1-deficient rhabdoid tumor cells. The lethal phenotype associated with snr1 knockdown in Drosophila melanogaster could be shifted to later stages of development upon additional knockdown of several decapentaplegic pathway members including Smox, and Med. Similarly, the transforming growth factor beta (TGFbeta) receptor type I kinase inhibitor SB431542 ameliorated the detrimental effect of snr1 knockdown in the fruit fly. Examination of homologs of candidate decapentaplegic pathway members in human SMARCB1-deficent ATRT samples revealed SMAD3 and SMAD6 to be over-expressed. In SMARCB1-deficent rhabdoid tumor cells, siRNA-mediated silencing of SMAD3 or SMAD6 expression reduced TGFbeta signaling activity and resulted in decreased proliferation. Similar results were obtained upon pharmacological inhibition of TGFbeta signaling using SB431542. Our data suggest that SMAD dependent signaling is involved in the detrimental effects of SMARCB1-deficiency and provide a rationale for the investigation of TGFbeta targeted treatments in ATRT
Published online: 20 January 2017
Gesehen am 20.08.2018